Supervisi Akademik IHT Untuk Meningkatkan Kemampuan Guru Dalam Menggunakan Media Pembelajaran - Putra , Wahyudi; Connie (UNIVERSITAS BENGKULU, 2024)
This study aims to describe the implementation of IHT academic supervision techniques to enhance teachers' competence in utilizing ICT-based learning media at SMA IT Ma’had Rabbani Bengkulu Tengah. The research design is a Supervisory Action Research. Data were collected using observation, instruments, and document analysis. Findings revealed a substantial improvement, with teachers' utilization of ICT-based learning media increasing from 20% in the pre-cycle to 100% after three cycles of IHT academic supervision. Competence in using these media scored an average of 79 in the first cycle, significantly improving to an average score of 90 in the second cycle, and further increasing to an average score of 94 in the third cycle.